Culturally and linguistically diverse learners and STEAM : teachers and researchers working in partnership to build a better tomorrow - Spycher, Pamela; Haynes, Erin F. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Multilingual students, multidialectal students, and students learning English as an additional language constitute a substantial and growing demographic in the United States. But these groups of students tend to receive unequal access to and inadequate instruction in Science, Technology, Engineering, Arts, and Mathematics (STEAM), with their cultural and linguistic assets going largely unacknowledged and underutilized. The need for more information about quality STEAM education for culturally and linguistically diverse students is pressing. This book seeks to address this need, with chapters from asset-oriented researchers and practitioners whose work offers promising teaching and learning approaches in the STEAM subjects in K-16 education settings. Authors share innovative ways in which classroom teachers integrate disciplinary reading, writing, discussion, and language development with content knowledge development in STEAM subjects. Also shared are approaches for integrating indigenous epistemologies, culturally sustaining pedagogy, and students' linguistic resources and life experiences into classroom teaching"--